Pengembangan Pop Up Book Interaktif Sebagai Media Pembelajaran Tata Cara Berwudhu Bagi Anak Usia 4-5 Tahun - Rifa Oktavia; Edo Dwi Cahyo (Jurnal Kajian Anak (J-Sanak), 2026)
This study aims to develop an interactive pop-up book as a learning tool on the proper ay to perform wudhu for early childhood students aged 4–5 years and to evaluate the feasibility of the developed tool. This study employs a Research and Development (R&D) method using the Borg and Gall development model, hich consists of ten stages: Research and Data Collection, Planning, Development, Preliminary Product Design, Preliminary Field Testing, Major Product Revision, Major Field Testing, Operational Phase, Operational Product Revision, Final Product Revision, Dissemination, and Implementation. The interactive pop-up book as developed to feature 3D images, attractive colors, and content regarding the wudhu procedure tailored to the characteristics of early childhood. Validation as conducted by subject matter experts, media experts, and language experts to assess the media’s suitability for learning. The validation results sho ed that the media received a “highly suitable” rating, ith 97% approval from subject matter experts, 90% from media experts, and 80% from language experts. A pilot test as conducted ith 27 children in kingdergarten A ages 4-5 and sho ed that the media as able to increase the children’s interest, engagement, and understanding of the sequence of wudhu procedures. Children found it easier to understand the steps of wudhu through play and practice. Thus, the media is effective for teaching wudhu to young children.